Interpersonal communication - Trenholm, Sarah (Wadsworth, 2000)
This text's five-step learning model helps students improve interpersonal competence in well-defined ways-through conceptual understanding, modeling of realistic examples, practicing of skill-building exercises, self-assessment, and translating learning into behavior. Intended for the instructors who take a theory/research approach